Additional Twists of Yarn Produced by System of Compact Spinning with Lattice Apron - 薛文良 魏孟媛 程隆棣 钱竞芳 (东华大学学报（英文版）, 2011)
Based on the flow simulation in the condensing zone of compact spinning with lattice apron and a bead-elastic rod dynamic model of the flexible fiber, trajectories of fibers with different negative pressure are simulated by specially designed Matlab procedure. Then displacement components of fibers at YZ profile under different negative pressure conditions are extracted and compared. The results show that the fibers of different initial positions gradually converge, and are interlaced for position change in yarn cross-section, caused by the airflow in the condensing zone. Finally, compact-spun yarn with different negative pressure and conventional ring spun yarn are produced and their twists are tested. Both the results of simulation and experiments illustrate the existence of additional twists. Also the relationship between additional twists and negative pressure is verified.